BODE INDEX IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE IN COMBINATION WITH HYPERTENSIVE HEART DISEASE - Kapustnyk, V.A.; Kostyuk, I.F.; Melenevych, A.Ya.; Tverezovskyi, V.M. (World of Medicine and Biology, 2020)
The prognostic potential of the BODE index in assessing future cardiovascular risk in patients with chronic obstructive pulmonary disease in combination with hypertensive heart disease based on left ventricular geometry has been established. Comparing the BODE index results depending on the type of left ventricular remodeling, a significant (p=0.032) increase in the index was determined in patients with prognostically unfavorable left ventricular remodeling compared to relatively favorable types – 1.73±0.45 scores vs. 1.45±0.63 scores. Patients with comorbid conditions showed a significant decrease in exercise tolerance and a tendency to desaturation. In order to increase the BODE index sensitivity in predicting the course of chronic obstructive pulmonary disease of the GOLD 2 grade, group B in combination with stage II hypertension, we propose to consider the presence of desaturation. That is, to consider a decrease in the saturation levels during a six-minute walk test from the initial value ≥4% as one of the prognostically unfavorable criteria.